A comparative study of a child's consent to medical treatment between Malaysia, United Kingdom, and Australia / Fatin Aina Ramli, Norsyuhada Nordin and Fatin Syuryati Hassan - Ramli, Fatin Aina; Nordin, Norsyuhada; Hassan, Fatin Syuryati (2012)
The issue of a child's consent to medical treatment are not widely discussed in Malaysia. This research aims to determine whether in Malaysia a child patient can give a valid consent in law to his or her medical treatment. The issue of whether a patient who is still a child has the right to give consent to medical treatment needs to be researched and discussed in order to give clarity and certainty to the law so that it can in turn be used as the basis for medical and legal practice. The examination on rules, regulations, and policies are being observed in order to obtain a clearer picture on the status quo of a child's consent to medical treatment in Malaysia. Amongst the rules and regulations are the Age of Majority Act 1971, Child Act 2001, Children & Young Persons Employment Act 1966, Guardianship of Infants Act 1961, Guidelines by Malaysian Medical Council (MMC), and etc. From examining these legislations, it can be concluded that currently Malaysia does not have a specific law that governs a child giving consent to medical treatment. Apart from discussing the current laws in Malaysia, the legal framework of a child's consent to medical treatment from the United Kingdom and Australia will also be discussed. Unlike Malaysia, the laws between the two countries mentioned before have provided rights to a child in terms of giving consent to medical treatment.